1961
DOI: 10.1126/science.133.3466.1766
|View full text |Cite
|
Sign up to set email alerts
|

"Bioconvection Patterns" in Cultures of Free-Swimming Organisms

Abstract: The moving polygonal patterns in dense cultures of Tetrahymena and other ciliates and flagellates look like "Benard cells," but are not due to thermal convection. They seem to be due to a similar dynamic instability that occurs when the energy input is internal and mechanical. The high concentration in the patterns may be useful in fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
154
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(159 citation statements)
references
References 4 publications
4
154
0
1
Order By: Relevance
“…[15,41,42]. However, the instability reported herein for magnetotactic bacteria lacks a key ingredient usually involved in the previously mentioned phenomenology.…”
Section: Discussion: Challenging Theoriesmentioning
confidence: 77%
“…[15,41,42]. However, the instability reported herein for magnetotactic bacteria lacks a key ingredient usually involved in the previously mentioned phenomenology.…”
Section: Discussion: Challenging Theoriesmentioning
confidence: 77%
“…Direct thermal convection can occur in micro-organism suspensions if the containing chamber is heated from below or from the sides, or if sufficient heat is absorbed from the illumination. However, bioconvection continues in a layer that is strongly cooled from below, so it is not a thermal effect (Platt, 1961). The radius, a, of a typical gyrotactic cell is approximately 5 × 10 −4 cm and the specific gravity is approximately 0.05.…”
Section: Introductionmentioning
confidence: 99%
“…Classical studies in bioconvection were largely mobilized by Platt (1961) who examined bioconvection patterns in cultures of free swimming organism and concluded that the moving polygonal patterns in Tetrahymena, ciliates and flagellates cultures which resemble Benard cells are not due to thermal convection but generated as a result of a dynamic instability due tointernal and mechanical energy input. Much later, Xu (2015) used Lie group analysis to investigate bioconvection flow of a nanofluid in a power law streaming flow.…”
Section: Introductionmentioning
confidence: 99%